Hepatocyte nuclear factor 4α regulation of bile acid and drug metabolism - Chiang, John YL (2009)
The hepatocyte nuclear factor 4α (HNF4α) is a liver-enriched nuclear receptor that plays a critical role in early morphogenesis, fetal liver development, liver differentiation and metabolism. Human HNF4α gene mutations cause maturity on-set diabetes of the young type 1, an autosomal dominant non-insulin-dependent diabetes mellitus. HNF4α is an orphan nuclear receptor because of which the endogenous ligand has not been firmly identified. The trans-activating activity of HNF4α is enhanced by interacting with co-activators and inhibited by corepressors. Recent studies have revealed that HNF4α plays a central role in regulation of bile acid metabolism in the liver. Bile acids are required for biliary excretion of cholesterol and metabolites, and intestinal absorption of fat, nutrients, drug and xenobiotics for transport and distribution to liver and other tissues. Bile acids are signaling molecules that activate nuclear receptors to control lipids and drug metabolism in the liver and intestine. Therefore, HNF4α plays a central role in coordinated regulation of bile acid and xenobiotics metabolism. Drugs that specifically activate HNF4α could be developed for treating metabolic diseases such as diabetes, dyslipidemia and cholestasis, as well as drug metabolism and detoxification.